The unconscious thinking processes of students - Kuldas, Seffetullah (2011)
The purpose of this study was to investigate the factors underlying thinking processes of master degree students, with regard to their demographical factors, in the Faculty of Education at University Technology Malaysia. It was to enhance an understanding of how students’ thinking processes work from the perspective of Freudian unconscious mind theory that every psychic action starts unconsciously. An exploratory research with quantitative and qualitative methods was conducted on 314 cases. The factors underlying students’ thinking processes were identified by a maximum likelihood extraction method of exploratory factor analysis with direct oblimin-Kaiser Normalization. Three extracted factors solution namely “Rationalization,” “Repression,” and “Unconscious association,” were displayed having an eigenvalue greater than 1.0 with Cronbach’s alpha value of 0.92. These factors were explaining well enough the total variance by the value of 58.1%. Each extracted factor met the requirement of being a factor by loading size of 0.4 and above in rotated pattern matrix. An independent samples t-test and a one-way ANOVA between groups provided no significant differences between “Males and Females,” “Malay and Non-Malay,” “Muslim and Non-Muslim,” and between “Age Groups” on the factors underlying their thinking processes. A Chi-square test for independence yielded no significant relationship between the groups of Gender, Age, Ethnic, Religion and their made choices. Comments from the respondents showed interesting indication on the students’ thinking processes based on the unconscious desirable and undesirable thoughts. These findings indicated that the ways the students engaged in their thinking activities were quite the same based on the tested variables. It implies that the factors underlying students’ thinking processes could be related to the other elements out of their conscious awareness. Accordingly, several suggestions and recommendations were provided for future references especially in explaining the students’ thinking processes further.